(1) a(b+c) + d(b+c) = 6
take (b+c) out
(b+c) * (a+d) = 6.
(2) (a+d) = 4
combining 1 and 2, b+c = 6/4
I know the answer, and I got the right answer, but I simply forgot some of the algebra that would allow me to get there. Can someone detailedly go through the algebra of this problem? I get the combining like terms part, and also get up to the part of getting a(b+c) + d(b+c) = 6. It's the just rest that where I get kind of hazy. And I'm writing this from memory, so I'm not quite sure if statement is really supposed to equal 6 or not. But I'm guessing that the actual numerical doesn't matter so much.
What is the value of b+c?(1) ab+cd+ac+bd = 6
(2) a + d = 4
There are currently 1 users browsing this thread. (0 members and 1 guests)